Active Smoking Induces Aberrations in Digestive Tract Microbiota of Rats - Wang, Xiang; Ye, Pei; Fang, Li; Ge, Sheng; Huang, Fan; Polverini, Peter J.; Heng, Weiwei; Zheng, Lichun; Hu, Qingang; Yan, Fuhua; Wang, Wenmei (Frontiers in Cellular and Infection Microbiology, 2021)
Cigarette smoking could have certain effects on gut microbiota. Some pioneering studies have investigated effects of active smoking on the microbiome in local segments of the digestive tract, while active smoking-induced microbiome alterations in the whole digestive tract have not been fully investigated. Here, we developed a rat model of active smoking and characterized the effects of active smoking on the microbiota within multiple regions along the digestive tract. Blood glucose and some metabolic factors levels, the microbial diversity and composition, relative abundances of taxa, bacterial network correlations and predictive functional profiles were compared between the control group and active smoking group. We found that active smoking induced hyperglycemia and significant reductions in serum insulin and leptin levels. Active smoking induced region-specific shifts in microbiota structure, composition, network correlation and metabolism function along the digestive tract. Our results demonstrated that active smoking resulted in a reduced abundance of some potentially beneficial genera (i.e. Clostridium, Turicibacter) and increased abundance of potentially harmful genera (i.e. Desulfovibrio, Bilophila). Functional prediction suggested that amino acid, lipid, propanoate metabolism function could be impaired and antioxidant activity may be triggered. Active smoking may be an overlooked risk to health through its potential effects on the digestive tract microbiota, which is involved in the cause and severity of an array of chronic diseases.